Deafness in children: a national survey of aetiological investigations. Issue 5 (13th September 2012) - Rangan, Shankar; Borgstein, Bernie; Lowe, Janet
Abstract : Objective: The aim of this study was to obtain national data regarding adherence to national guidelines for aetiological investigations for hearing loss in children and highlight any variations in practice. Information was also collected on possible factors affecting lack of adherence. Design: An online questionnaire based on the national guidelines for aetiological investigations for deafness was designed. Setting: The questionnaire was distributed to the leads of all the Newborn Hearing Screening Programme (NHSP) sites across England through the Medical Research Council Hearing & Communication Group. Participants: The questionnaire was sent to 100 recipients; from this 52 responses were obtained. Outcome measures: Variability in the investigations offered for hearing loss. Results: There was a 52% response rate. Analysis of the responses showed that audiovestibular physicians and paediatricians in audiology were more likely than other specialists to request level 1 investigations (investigations that are recommended to be offered in all cases). Respondents from London and the North West were more likely to request level 1 investigations compared with those from other regions. In all, 14 of the 19 audiovestibular physicians and paediatricians in audiology requested level 1 investigations routinely, but only 11 of 33 from other specialties did likewise. Of the 20 respondents from London and the Northwest, 15 requested level 1 investigations routinely, whereas only 10 of the 32 respondents from the other regions did the same. The difference was statistically significant in both cases. The geographical variation was specially marked for family audiograms and MRI. Conclusions: There is significant variation from the national guidelines in requesting aetiological investigations for permanent hearing impairment (PHI) in children, depending on the specialty of the clinician and the geographical region, these variations appear partly to be due to the availability of local resources but also due to lack of awareness of the importance of some investigations.